The use of meshes in male groin hernia repairs. Issue 4 (21st July 2021) - Banerjee, Abhirup; Bhattacharya, Satyajit
Abstract : The use of a mesh is standard practice in the surgical repair of groin hernias. No one type of mesh or surgical technique appears to be superior to another. Here the authors discuss the evolution of groin hernia repair, the different types of mesh, as well as the investigation and management of complications that can occur, albeit in a minority of patients.